Producing the ‘Trafficked Woman’: Canadian Newspaper Reporting on Eastern European Exotic Dancers During the 1990s - Durisin, Elya M.; Heynen, Robert (Atlantis)

(untitled) (Mount Saint Vincent University, 2015)
This article explores the emergence of discourses of “human trafficking” in Canadian newspapers during the 1990s, focusing on the depiction of Central and East European migrant women. The period saw much debate over a work permit exemption in federal immigration policy that allowed for the migration of workers into the exotic dance sector. We argue that debates over the exemption were often framed through an ethnosexualizing discourse that enabled narratives of victimization and legitimated repressive border security and policing practices.